Model Manajemen Kurikulum Pendidikan Agama Islam Berbasis Integrasi Ilmu dan Iman - Nurjaman, Azi (Lembaga Pengkajian Pengembangan Pendidikan dan Kewirausahaan, 2026)
This study aims to deeply understand and analyze the dynamics of Islamic Religious Education (PAI) curriculum management based on the integration of science and faith from a qualitative perspective. The background of this study is the challenge of value disorientation and the dichotomy of science in contemporary education, which emphasizes the urgency of aligning the cognitive, affective, and spiritual aspects of students. This study focuses on how the process of planning, implementing, and evaluating the PAI curriculum holistically combines general scientific material with the values ??of faith and Islamic teachings. The research method uses a qualitative approach with a case study design, involving the principal, PAI teachers, and curriculum coordinator at a madrasah in Bandung. Data were collected through in-depth interviews, participant observation, and document analysis. The results of the study indicate that the integration of science and faith in PAI curriculum management requires a strong conceptual understanding, institutional commitment, and pedagogical adaptation from teachers. This integration process significantly influences teachers' and students' perceptions of the relevance of PAI and encourages holistic understanding. The implications of this study are the importance of teacher professional development and systemic support to realize a curriculum that is not only intellectually intelligent, but also has an Islamic character and is aware of the relevance of science in a faith perspective.